The Relationship of Prime-HRM Implementation on Employee Work Performance of Prime-HRM Level II (Bronze) Agencies in General Santos City - Tubiano, Angelica Halago; Echalar, Lovely Vegafria (International Journal of Research in Interdisciplinary Studies, 2025)
The purpose of the study was to determine the extent of implementation of Program to Institutionalize Meritocracy and Excellence in Human Resource Management (PRIME-HRM) and its correlation to employee work performance in government agencies of General Santos City. Descriptive-correlational research design was employed, involving 335 respondents coming from GSCWD, DepEd, and LGU-GSC through the use of survey questionnaires and key informant interviews. Descriptive statistics, Mann-Whitney U, Kruskal-Wallis, and Spearman Rank Correlation tests were used to analyze quantitative and thematic analysis was used to explore qualitative responses. Results indicates that PRIME-HRM practice is relatively high across all HRM functions, especially recruitment, selection and placement, and that this is positively and significantly associated with employee work performance. Work quality, efficiency, and timeliness were highly rated and there were no significant differences among demographic factors. Challenges on capacity gaps as well as technological resistance, lack of information and resource limitations are identified. The research finds that PRIME-HRM has a significant impact on increasing work performance among employees across their demographic background but it is recommended that there should be ongoing communications, training and resource support for the continued enhancements. These results suggest for policymakers and HR practitioners to build meritocracy systems and to boost the productivity of the public sector.